2007
DOI: 10.1200/jco.2007.11.5022
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-kB Tumor Expression Predicts Response and Survival in Irinotecan-Refractory Metastatic Colorectal Cancer Treated With Cetuximab-Irinotecan Therapy

Abstract: The difference in median TTP, overall survival, and response rate seem to confirm that NF-kB may play a crucial role in predicting the efficacy of cetuximab and irinotecan in advanced colorectal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…4). Expression of this transcription factor, also activated by the EGFR downstream signaling pathway, has been associated with prognosis and resistance to antitumoral treatments in CRC and other solid tumors (46). These data stress as different responses to cetuximab are related to different sets of differentially expressed miRNAs and, accordingly, to different molecular signaling.…”
Section: Discussionmentioning
confidence: 87%
“…4). Expression of this transcription factor, also activated by the EGFR downstream signaling pathway, has been associated with prognosis and resistance to antitumoral treatments in CRC and other solid tumors (46). These data stress as different responses to cetuximab are related to different sets of differentially expressed miRNAs and, accordingly, to different molecular signaling.…”
Section: Discussionmentioning
confidence: 87%
“…Constitutive NF-kB activation is found in most cancer cell lines and in numerous types of tumour tissues (Shishodia and Aggarwal 2004). Scartozzi et al (2007) reported that NF-kB nuclear expression predicts response and survival in irinotecan-refractory metastatic CRC treated with cetuximab -irinotecan therapy. These findings suggested that the tumour cell TLR4/MyD88 signalling pathway has a crucial role in CRC patient prognosis and that blocking this pathway could provide great benefits for patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason that a combination of cytostatic and alpha lipoic acid exerts an inhibitory effect on the NF-κB levels would be strong antioxidant properties of the alpha lipoic acid, which thereby reduce the inducible effect. But the fact that the ALA applied solely and thus was not being able to completely suppress the synthesis and the activation of the NF-κB, acknowledges that cancer cells produce a constitutive NF-κB not only in response to the epigenetic factors (oxidative stress), but most likely as a mode for their survival (25,26,27). This is why it is inexplicable that the combined use of lipoic acid and 5-FU has resulted in increased effect of the cytostatic applied.…”
Section: Discussionmentioning
confidence: 99%